Clinical symptoms and their relationship with cognitive impairment in elderly patients with depressive disorder - Wu, Zhenguo; Su, Guanli; Lu, Wenting; Liu, Lin; Zhou, Zixuan; Xie, Bingchuan (Frontiers in Psychiatry, 2022)
Objective: To evaluate the correlation between clinical symptoms and cognitive impairment in elderly patients with depressive disorder Methods: In this retrospective study, a total of 123 elderly patients with depressive disorder admitted to our hospital from January 2020 to February 2021 were included. Patients’ cognitive function was assessed by the Montreal Cognitive Assessment Scale (MoCA). According to the combination of cognitive impairment or not, patients were divided into the combined group (64 cases) and the depressive disorder group (59 cases). In addition, 70 healthy people who came to our hospital for physical examination during the same period were randomly selected as the healthy group. Results: The incidence of severe cognitive impairment in the combined group (33, 51.56%) was significantly higher than that in the depression group (19, 32.20%), the difference was statistically significant (P=0.003). The incidence of somatization symptoms, suicidal tendency, retardation of thinking, diminution of energy, anxiety and sleep disorder in the combined group were higher than that in the depressive disorder group with significant difference [30(56.88%) vs. 16 (27.12%), P=0.024; 12 (18.75%) vs. 3 (5.08%),P=0.021; 33 (51.56%) vs. 14 (23.73%),P=0.002; 37 (57.81%) vs. 23 (38.98%), P=0.029; 42 (65.63) vs. 25 (42.37), P=0.011; 50 (78.13) vs. 42 (71.19), P=0.031, respectively). Spearman rank correlation analysis suggested that somatic symptom, mood change, suicidal tendency, retardation of thinking, diminution of energy, anxiety, and sleep disorder were negatively correlated with cognitive impairment, respectively (r =-0.161, -0.672, -0.262, -0.871, -0.421, -0.571, -0.512, P < 0.001). Conclusion: The clinical symptoms of depressive disorder were negatively correlated with cognitive impairment. Somatic symptoms, suicidal tendency, retardation of thinking, diminution of energy, anxiety, and sleep disorder were the risk factors for cognitive impairment.